Optimalisasi Peran Guru Dalam Meningkatkan Kemampuan Membaca Siswa - Supriyadi, Supriyadi (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2023)
This research aims to analyze the role of teachers in improving the reading skills of class II students at SDN 3 Kedungwinangun. This research is qualitative research. The subjects of this research were 2nd grade students at SDN 3 Kedungwinangun. Research data was taken using test techniques. The research results were analyzed using interactive analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results of the research show that optimizing the teacher's role in learning improves the reading ability of class II students at SDN 3 Kedungwinangun, Klirong District, Kebumen Regency through providing thematic lesson plans using the picture and picture model, providing word cards and letter cards, reading corners in the classroom, providing literacy trees. There is an increase in students' reading skills through learning activities by applying the picture and picture learning model, there are literacy activities at the beginning of learning, and there are evaluation activities to improve subsequent learning.